2024
DOI: 10.1039/d3se01216f
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of residual biomass by pyrolysis: influence of process conditions on products

A. C. M. Vilas-Boas,
L. A. C. Tarelho,
H. S. M. Oliveira
et al.

Abstract: In the context of sustainable residual biomass management, this work explores the pyrolysis process of residual biomass using a bench-scale fixed bed reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…The study conducted by Hanafi et al 45 found that biochars with a volatile matter content of 40% exhibited a breakdown rate of less than 10% over 100 years. The higher volatile matter content found in eggplant residue-derived biochar may serve as a valuable source of easily decomposable carbon (labile carbon) for microbial populations, as demonstrated by Vilas-Boas et al 46 . However, this greater volatile matter content could potentially have adverse effects on carbon storage, as it may lead to a positive priming impact.…”
Section: Discussionmentioning
confidence: 92%
“…The study conducted by Hanafi et al 45 found that biochars with a volatile matter content of 40% exhibited a breakdown rate of less than 10% over 100 years. The higher volatile matter content found in eggplant residue-derived biochar may serve as a valuable source of easily decomposable carbon (labile carbon) for microbial populations, as demonstrated by Vilas-Boas et al 46 . However, this greater volatile matter content could potentially have adverse effects on carbon storage, as it may lead to a positive priming impact.…”
Section: Discussionmentioning
confidence: 92%
“…During biochar production, pyrolysis temperature plays a key role in the thermochemical conversion of biomass [13,[16][17][18][19]23,24]. In general, biomass heated to high temperatures (>500 • C) produces biochar with a porous structure, large specific surface area (SSA), aromaticity, C-C content, and high pH, while those made at low temperatures (<400 • C) have a high yield and O/C and H/C ratio, and low electrical conductivity (EC), cation exchange capacity, and surface functional groups [16][17][18][19]25].…”
Section: Introductionmentioning
confidence: 99%